The Library and the Modern Mind: Paratexts of Library Space. - Jarvis, Ewen David (International Journal of the Humanities, 2006)
‘The Library and the Modern Mind’ represents a component of my research into the history and nature of libraries and book collections for my PhD thesis (through the School of Communication and Creative Arts at Deakin University). In ‘The Library and the Modern Mind’ I will discuss the nature of libraries and consider how they operate within society and how they affect society. When you enter the liminal space of a library what cultural baggage is involved? What expectations do you have? What restraints are there? Who chooses what material is acquired and discarded? Who presides over the accumulated knowledge? Can intellectual freedom be achieved? In answering these questions I will consider the history of libraries and the changes they face. I will compare how libraries perceive themselves with how their users see them. I will consider the ways in which libraries both agitate and restrain the social organism. And I will view the form and function of libraries through various philosophical lenses. Is a library a machine for the retrieval of information? Is it a structure of power? Is it a sign that points to a signified? Is it structured like Lacan's unconscious (which is structured like a language), or can it be compared to a rhizomatic structure (a structure without hierarchy). In what ways does it mirror society, and how does the library space compare with cyberspace? Finally, I will consider how libraries should position themselves in the information age and what their role should be within an always uncertain consumer culture.